2011
DOI: 10.3758/s13421-011-0091-2
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive memory: Stereotype activation is not enough

Abstract: Studies have shown that survival processing leads to superior memorability. The aim of the present study was to examine whether this survival recall advantage might result from stereotype activation. To test this hypothesis, we conducted a pilot study and two experiments in which participants were primed with stereotypes (Experiment 1, professor and elderly person; Experiment 2, survival-stereotype). In Experiment 1, 120 undergraduates were randomly assigned to a survival, professor stereotype, elderly person … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
21
1
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 29 publications
5
21
1
4
Order By: Relevance
“…The survival encoding strategy leads to excellent retention [1], [6][12] and these findings have been corroborated and extended by other labs [13][17]. It appears unlikely that the memorial potency of survival processing can be sufficiently explained by a mediating factor of emotional arousal [15], [16] or stereotype activation [18].…”
Section: Introductionsupporting
confidence: 56%
“…The survival encoding strategy leads to excellent retention [1], [6][12] and these findings have been corroborated and extended by other labs [13][17]. It appears unlikely that the memorial potency of survival processing can be sufficiently explained by a mediating factor of emotional arousal [15], [16] or stereotype activation [18].…”
Section: Introductionsupporting
confidence: 56%
“…While it has been convincingly shown that survival-related processing can boost memory across different types of stimuli, memory domains, and research populations (Aslan & Bä uml, 2012;Burns, Burns, & Hwang, 2011;Burns, Hart, Griffith, & Burns, in press;Kang, McDermott, & Cohen, 2008;Kostic, McFarlan, & Cleary, 2012;Nairne, Pandeirada, & Thompson, 2008;Nairne, VanArsdall, Pandeirada, & Blunt, 2012;Otgaar et al, 2011;Otgaar, Howe, Smeets, Raymaekers, & van Beers, in press;Otgaar, Smeets, & van Bergen, 2010;Raymaekers, Smeets, Otgaar, Peters, & Merckelbach, in press;Smeets, Otgaar, Raymaekers, Peters, & Merckelbach, 2012;Weinstein, Bugg, & Roediger, 2008; but see Klein, 2012;Seamon et al, 2012), a common feature of all previous studies is that they were concerned with illustrating the beneficial effects of survival processing in the short run (typically 2Á3 minutes, maximum 10 minutes, see Savine, Scullin, & Roediger, 2011). Thus far not a single study has investigated the persistence of the survival recall advantage after extended delay periods.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…In the years since Nairne et al's (2007) original study testing the survival processing advantage, several studies have further confirmed their results with the same, and some additional, comparison encoding tasks (e.g., a bank robbery scenario, Kang, McDermott, & Cohen, 2008; professor and elderly stereotype scenarios, Otgaar et al, 2011;itemspecific or relational processing, Burns, Burns, & Hwang, 2011; and a city survival scenario, Weinstein, Bugg, & Roediger, 2008). Studies have also generalized the survival processing advantage to picture stimuli (Otgaar, Smeets, & van Bergen, 2010) and to location memory (Nairne, VanArsdall, Pandeirada, & Blunt, 2012).…”
mentioning
confidence: 78%